Hemicellulose-based hydrogel composite: Enhanced properties and diverse applications - Andi Fadiah Ainani; Darmawan; Joko Tri Rubiyanto; Maulana Nur Ardian; Widya Nur Habiba; Adiansyah Syarifuddin; Andi Dirpan (Carbohydrate Polymer Technologies and Applications)
Hemicellulose hydrogels have garnered significant attention owing to their abundance and exceptional properties, such as renewability and biodegradability. However, their weak mechanical strength and poor stability limit their application across various fields. The addition of other materials (composites) and modification with different synthetic monomers can improve the mechanical properties and stability of these hydrogels. Therefore, research efforts are increasingly focused on exploring composite preparation and synthesis methods. This review discusses the isolation and synthesis of hemicellulose-based hydrogel composites, along with their development and applications across various sectors. In addition, it presents the current state of research and emerging trends, offering a prospective study on the potential expansion of hemicellulose-based hydrogel composites in fields such as biomedicine, sensors, and waste treatment. The findings suggest that hemicellulose-based hydrogel composites are becoming increasingly popular as advanced materials. By utilizing innovative composite preparation techniques and synthesis methods, these hydrogels are poised to revolutionize various sectors such as biomedical, sensors, and agricultural, offering solutions with improved mechanical properties and stability.